Engineering of a zero cross-talk fluorescent polymer nanoprobe for self-referenced ratiometric imaging of lysosomal hypochlorous acid in living cells. (17th January 2020) - Wei, Hongqing; Zeng, Rongjin; Wang, Shenglan; Zhang, Chong-Hua; Chen, Shu; Zhang, Peisheng; Chen, Jian
Abstract : A zero cross-talk fluorescent polymer nanoprobe with a self-referenced ratiometric effect was rationally designed and synthesized for lysosomal hypochlorous acid (HClO) imaging in live cells. Abstract : The rational design of a zero cross-talk self-referenced ratiometric fluorescent probe for accurate molecular imaging in living cells is still a major challenge. Herein, we report a zero cross-talk fluorescent polymer nanoprobe (named ZC-FPN) with a self-referenced ratiometric effect for lysosomal hypochlorous acid (HClO) imaging using single-wavelength excitation. The newly designed polymer nanoprobe (ZC-FPN) is prepared by using a simple co-precipitation method through self-assembly of two amphiphilic block copolymers, which are covalently linked with a porphyrin fluorophore (HClO-responsive unit) and a naphthalimide fluorophore (reference unit), respectively. Remarkably, the ZC-FPN displays an unprecedented separation of two emission peaks (∼191 nm), which can avoid the spectral cross-talk problem of the emission-shift type ratiometric probes and is highly favorable for high-resolution bioimaging. In addition, the as-prepared ZC-FPN also shows good water dispersibility, high selectivity, excellent long-term fluorescence stability (>10 weeks) and low cytotoxicity. More importantly, the positive charge of the amino moiety enhances the efficient uptake of the nanoprobe by cancer cells and enables the nanoprobe to selectively accumulate in lysosomes, achieving endogenous HClO imaging in living cells through fluorescence ratiometric imaging.